Effects of Ivabradine on 6-Minute Walk Test and Quality of Life in Patients with Previously Implanted CRT-D. (August 2013) - Ates, Ismail; Yavuz, Asuman H.; Doğru, Mehmet; Genç, Ahmet; Ulucan, Şeref; Sarıkaya, Metin; Çetinkaya, Ramazan; Keser, Ahmet; Akpek, Mahmut; Kaya, Mehmet G.
Background: We aimed to evaluate clinical effects of additional heart rate control by ivabradine on life quality score and 6-minute walking test in patients with previously implanted biventricular cardiac resynchronization therapy defibrillator (CRT-D) with ischemic heart failure under regular treatment. Methods: Fifteen men and 14 women with a median age of 63 years (range, 48–79 years) were studied. Twenty-one patients were in New York Heart Association class II (8 patients were in class III), CRT-D implanted previously, and with resting heart rates greater than 70 beats per minute with sinus rhythm despite conventional medication. Patients were given 2.5- to 7.5-mg ivabradine orally twice a day, and drug dosage was titrated to decrease the patients' average heart rate to 70 beats per minute. Before and 3 months after ivabradine treatment, all patients underwent extensive clinical, echocardiographic, and laboratory evaluation. Results: Ivabradine treatment produced dose-dependent reductions in heart rate at rest and at peak exercise (91.9 ± 6.3 to 71.7 ± 4.8 and 114.4 ± 7.6 to 96.8 ± 4.8; P = 0.001 and P = 0.001, respectively). There were also significant improvements in life quality score (52.4 ± 9.5 to 37.9±7.8; P = 0.001) and 6-minute walking distance (278.7 ± 85.8 to 373.3 ± 94.0; P = 0.001) of patients. All patients with New York Heart Association class III became class II after 3 months of ivabradine treatment. Conclusion: Heart rate reduction in a short-term period by ivabradine produced significant improvements in exercise capacity and life quality in patients with CRT-D and conventional therapy.